(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Abdominal and retroperitoneal sarcomas are rare and heterogeneous. Despite a considerable number of sarcoma centres in Switzerland, only very limited data is available regarding clinical outcomes after primary surgical treatment. In this study, we retrospectively analysed a cohort of 157 patients treated at a Swiss sarcoma centre, aiming to assess whether the clinical outcomes in our cohort are comparable to those reported by international centres. METHODS: Overall, 271 patients with abdominal and retroperitoneal sarcomas, treated between January 2012 and December 2022, were available. Patients with malignant disease and primary resection were included. The primary endpoint was overall survival, while secondary endpoints included disease-free survival, incidence of histological subtypes, completeness of surgical resection and tumour rupture. RESULTS: Ultimately 157 patients with primary, resectable soft tissue sarcoma were included in the analysis. Median follow-up after surgery was 52.6 months (95% confidence interval [CI]: 42.24–62.95). Median overall survival was 87.9 months (95% CI: 54.95–120.74); by subgroup, 117.5 months for gastrointestinal stroma tumour (95% CI: 76.96–158.00), 61.8 months for liposarcoma (95% CI: 40.16–83.36), 117.8 months for leiomyosarcoma (95% CI not achieved) and 100.2 months for other rare subtypes (95% CI: 59.65–111.30). Forty-four (28%) patients developed tumour recurrence. CONCLUSIONS: Overall outcomes in this series are comparable to those from large international registries. A national data registry might help to improve reporting of clinical data and assure quality of care of Swiss sarcoma patients.